2007
DOI: 10.1093/nar/gkm210
|View full text |Cite
|
Sign up to set email alerts
|

On the stability of peptide nucleic acid duplexes in the presence of organic solvents

Abstract: Nucleic acid double helices are stabilized by hydrogen bonding and stacking forces (a combination of hydrophobic, dispersive and electrostatic forces) of the base pairs in the helix. One would predict the hydrogen bonding contributions to increase and the stacking contributions to decrease as the water activity in the medium decreases. Study of nucleobase paired duplexes in the absence of water and ultimately in pure aprotic, non-polar organic solvents is not possible with natural phosphodiester nucleic acids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 49 publications
(57 citation statements)
references
References 46 publications
3
53
0
1
Order By: Relevance
“…Interestingly, the application of hot formamide for the isolation of peptidoglycan is reported in the literature, which is in agreement with the proposed explanation (Fuller, 1938;Greenblatt et al, 1978;Perkins, 1965). As the preservation of cells integrity is crucial for a proper hybridization, bacteria with cell envelope damaged by FA would not benefit from its hybridization adjuvant function (Sen and Nielsen, 2007).…”
Section: Optimization Of Pna Eub338 By Rsmmentioning
confidence: 99%
“…Interestingly, the application of hot formamide for the isolation of peptidoglycan is reported in the literature, which is in agreement with the proposed explanation (Fuller, 1938;Greenblatt et al, 1978;Perkins, 1965). As the preservation of cells integrity is crucial for a proper hybridization, bacteria with cell envelope damaged by FA would not benefit from its hybridization adjuvant function (Sen and Nielsen, 2007).…”
Section: Optimization Of Pna Eub338 By Rsmmentioning
confidence: 99%
“…In a previous study on the effect of the aprotic, organic solvent DMF on the stability of iso-sequential PNA路PNA, PNA路DNA and DNA路DNA duplexes, we have shown that the change in the number of bound water molecules associated upon thermal melting of PNA路PNA duplexes is the smallest [21], and that PNA duplexes (in contrast to DNA duplexes) show almost unaffected stability in 70% DMF [22]. In order to assess the contributions from stacking forces and H-bonds to the thermal stability of the duplexes of the present study, we have investigated the effect of increasing amount of DMF on the thermal stabilities of the PNA duplexes containing D base and/or bT base ( Figure 2; thermal and thermodynamic data are presented in Tables S2-S6 with representative thermal melting curves in Figures S4 and S5, and the corresponding plots in Figure S6).…”
Section: Effect Of Dmfmentioning
confidence: 94%
“…However, increasing temperature as well as pH, and the presence of organic solvents including DMSO, weaken the stability of PNA duplexes, 30 and therefore, conditions that favor chemical acyl transfer disfavor hybridization including hairpin formation. Therefore, we measured the thermal stability of PNA 3751 in the presence of DMSO in order to elucidate the importance of the "hairpin structure" for Phe-transfer.…”
Section: Acs Chemical Biologymentioning
confidence: 99%